2000
DOI: 10.1038/80489
|View full text |Cite
|
Sign up to set email alerts
|

Secretory leukocyte protease inhibitor mediates non-redundant functions necessary for normal wound healing

Abstract: Secretory leukocyte protease inhibitor (SLPI) is a serine protease inhibitor with anti-microbial properties found in mucosal fluids. It is expressed during cutaneous wound healing. Impaired healing states are characterized by excessive proteolysis and often bacterial infection, leading to the hypothesis that SLPI may have a role in this process. We have generated mice null for the gene encoding SLPI (Slpi), which show impaired cutaneous wound healing with increased inflammation and elastase activity. The alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
324
2
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 377 publications
(357 citation statements)
references
References 42 publications
25
324
2
6
Order By: Relevance
“…Measurement of these parameters are not only essential to monitor the absence of local inflammation in bone chamber implants but also necessary to understand the complex interactions of the microenvironment in bone tissue. Several observations confirm that leukocytes play an important role in fracture repair and wound healing and a disturbance of leukocyte homeostasis in tissue leads to impairment of tissue regeneration [5,6,26,41,44]. Here we present for the first time the time-dependent alterations in interactions between leukocytes and endothelium of bone vessels quantitatively, following a surgical procedure to bone.…”
Section: Discussionsupporting
confidence: 60%
“…Measurement of these parameters are not only essential to monitor the absence of local inflammation in bone chamber implants but also necessary to understand the complex interactions of the microenvironment in bone tissue. Several observations confirm that leukocytes play an important role in fracture repair and wound healing and a disturbance of leukocyte homeostasis in tissue leads to impairment of tissue regeneration [5,6,26,41,44]. Here we present for the first time the time-dependent alterations in interactions between leukocytes and endothelium of bone vessels quantitatively, following a surgical procedure to bone.…”
Section: Discussionsupporting
confidence: 60%
“…Recently Ashcroft et al (52) reported that SLPI-null mice had impaired cutaneous wound healing with increased inflammation. Our results imply that SLPI plays a role in controlling the inflammatory response in the acute cutaneous wound during phagocytosis of apoptotic cells, and may help to explain why wound healing is impaired in SLPI-null mice (52).…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that Pdp11 may avoid deleterious effects in skin. In addition, it was found that LEI has antimicrobial properties in mucosal fluids [57] and is up-regulated by cytokines such as interleukin-1 (IL-1) and tumor necrosis factor (TNF) [58]. Based on this, LEI under-expression in overcrowding stress fish may suggest an increased susceptibility of skin to infections.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%